(untitled) (Journal of Nepal Geological Society, 1998)
The low grade pre-Tertiary metamorphic nappe rocks, underlying widely exposed high grade crystalline rocks in eastern Himalaya, override the narrow frontal belt of Neogene Siwalik molasse sediments along the Main Boundary Thrust (MBT). Marine Eocene or early Miocene sediments are only exposed as narrow thrust slivers over wide lateral extent close to and beneath the MBT, and also within the northern parts of the Neogene sediments. The slivers of pre-Tertiary rocks within the Neogene belt have two modes of occurrence, more frequently they occur as klippen over the Neogene sequence and floored by the MBT, or as basement wedge, which at times preserve unconformable relation with the Neogene cover. Domal window structures in eastern Himalaya, north of frontal belt, expose low grade pre-Tertiary metasediments occurring beneath the crystalline nappe. The largest Siang window located close to eastern syntaxis of the Himalaya, is distinctive and exposes a duplex arch of late Palaeocene-Eocene sediments and the Abor volcanic rocks. The MBT represents the folded roof-thrust of the window. The overlying Himalayan pre-Tertiary nappe rocks are passively folded. The Siang and other windows from eastern Himalaya, located at the external fringes of the Himalayan nappe sheets, have many structural similarities. These are inferred to have evolved in a similar way and during the process of emplacement of the crystalline and low grade pre-Tertiary Himalayan nappes over the Tertiary foreland basin. During the early-mid Eocene period, contemporaneous to terminal collision at the northern margin of the Himalaya, there was continental flood basalt and other volcanic extrusion in the foreland basin located at the marginal parts of the Himalayan fold-thrust belt. The Eocene foreland rocks at present are largely tectonically concealed. Thrust movements involving the pre-Tertiary Himalayan nappes, the subjacent Tertiary sub-thrust rocks and their architecture influenced the structure of the Himalayan nappes at their external fringes and often-formed duplexes and windows. The Siang window was possibly produced by the interaction between the NE projecting indenture of the Indian continent that acted as an oblique crustal ramp over which the Himalayan and Trans-Himalayan nappes were propagated. Several nappes in the eastern limb of the dome are greatly attenuated in width and are overridden by the frontally advanced Trans-Himalayan granitoid nappe. Convergence of tectonic movements at the eastern syntaxis produced imbricate thrusts and duplex arch in the sub-thrust Palaeogene rocks, which breached the MBT and passively folded overlying Himalayan nappes. The western limb of the complimentary synform, west of the Siang window, is obliquely truncated by a major N-S trending dextral tear-fault, which has also climbed from the floor-thrust of the Siang window and has breached the MBT as well as the Main Central Thrust (MCT). It resembles the imbricate thrusts within the Palaeogene rocks from the Siang window. In other windows, the sub-thrust Tertiary rocks appear to have played more passive role and may not have been tectonically arched up.